Colistin and Isavuconazole Interact Synergistically In Vitro against Aspergillus nidulans and Aspergillus niger - Patrick Schwarz; Elie Djenontin; Eric Dannaoui (Microorganisms, 2020)
The in vitro interactions of isavuconazole in combination with colistin were evaluated against 55 clinical Aspergillus species isolates belonging to the five most important species (Aspergillus flavus, Aspergillus fumigatus, Aspergillus nidulans, Aspergillus niger, and Aspergillus terreus) responsible for human aspergillosis by a microdilution checkerboard technique based on the European Committee on Antimicrobial Susceptibility Testing (EUCAST) reference method for antifungal susceptibility testing. Selected isolates (A. nidulans, n = 10; A. niger, n = 15) were additionally evaluated by an agar diffusion assay using isavuconazole gradient concentration strips with or without colistin incorporated Roswell Parc Memorial Institute (RPMI) agar. Interpretation of the checkerboard results was done by the fractional inhibitory concentration index. Using the checkerboard method, combination isavuconazole–colistin was synergistic for 100% of the 15 A. nidulans isolates and for 60% of the 20 A. niger isolates. No interactions were found for any of the other isolates. By agar diffusion assay, minimal inhibitory concentrations (MICs) in combination decreased compared to isavuconazole alone for 92% of the isolates. No interactions were found for any A. nidulans isolates, but synergy was observed for 40% of the A. niger isolates. A poor essential agreement of EUCAST and gradient concentration strip MICs at ± 2 log2 dilutions with 0% was obtained. Antagonistic interactions were never observed regardless of the technique used.